Family Matters: Promoting the Academic Adaptation of Latino Youth in New and Established Destination. (March 2017) - Spees, Lisa; Perreira, Krista M.; Fuligni, Andrew
As primary agents of socialization, families and schools can powerfully shape the academic adaptation of youth. Using data from the Social Identification and Academic Adaptation studies, we compare the family and school environments of Latino high school seniors living in a new destination, North Carolina, with those living in an established destination, Los Angeles. We then evaluate how family and school environments influence their educational aspirations, expectations, and performance. We find that parents' achievement expectations promote Latino youths' academic success, while perceived future family obligations inhibit them. Additionally, we find that schools remain essential in promoting Latino immigrant youths' achievement by providing a supportive and safe learning environment. Discrimination in schools and the broader community is associated with lower educational expectations and aspirations but not lower academic performance.